Learning strategies used by secondary school students in the course of history studies - (:unkn) unknown (EDAM, 2007)
The present study examined what teaching strategies are used by junior high school students and the ways students make history classes meaningful. The sample of the study was randomly chosen 346 students from three secondary public schools affiliated with the Ministry of National Education and located in the district of Uskudar, Istanbul. The study used both quantitative and qualitative research methods. In quantitative part, a pilot study was conducted and a questionnaire was prepared with the help of an expert group. In qualitative part, students' learning strategies were determined through personal interviews (n = 13). According to the findings, nearly half of the students stated that they liked history courses in every condition but they did not know how to study for this class. It was found that 19.7 % of the students got bored with the course because they did not know how to study for it and 73.13% of the students were trying to lea m this class by themselves. When studying history courses, the most used learning strategy is repetition and the least used strategy is giving meaning.
Keywords: society; learning culture; learning strategies; history teaching curricula; bringing up teachers